New species and records of Laena Dejean (Coleoptera: Tenebrionidae: Lagriinae) from Vietnam, southeastern China, and Korea - Schawaller, Wolfgang; Bellersheim, Aron (Zootaxa, 2023)
New species and new records of the genus Laena Dejean, 1821 from Vietnam, southeastern China (Hainan, Fujian, Guangdong, Guangxi, Guizhou, Jiangxi and Zhejiang provinces) and Korea are presented. The following new taxa are described: L. brunkei sp. n. (Vietnam, Guizhou), L. faillei sp. n. (Vietnam), L. honba sp. n. (Vietnam), L. tramtonica sp. n. (Vietnam), L. hainanica sp. n. (Hainan), L. hajeki sp. n. (Guangdong), L. lianhua sp. n. (Jiangxi), L. logshengica sp. n. (Guangxi, Fujian), L. yuanbaoica sp. n. (Guangxi). Laena rotundicollis Marseul, 1876 is recorded from Korea for the first time.